Effect of architecture on the formation of surface multilayer structures at the air-solution interface from mixtures of surfactant with small poly(ethyleneimine)s. - Halacheva, S; Penfold, J; Thomas, R; Webster, JR (2012)
The impact of ethyleneimine architecture on the adsorption behavior of mixtures of small poly(ethyleneimines) and oligoethyleneimines (OEIs) with the anionic surfactant sodium dodecylsulfate (SDS) at the air-solution interface has been studied by surface tension (ST) and neutron reflectivity (NR). The strong surface interaction between OEI and SDS gives rise to complex surface tension behavior that has a pronounced pH dependence. The NR data provide more direct access to the surface structure and show that the patterns of ST behavior are correlated with substantial OEI/SDS adsorption and the spontaneous formation of surface multilayer structures. The regions of surface multilayer formation depend upon SDS and OEI concentrations, on the solution pH, and on the OEI architecture, linear or branched. For the linear OEIs (octaethyleneimine, linear poly(ethyleneimine) or LPEI(8), and decaethyleneimine, LPEI(10)) with SDS, surface multilayer formation occurs over a range of OEI and SDS concentrations at pH 7 and to a much lesser extent at pH 10, whereas at pH 3 only monolayer adsorption occurs. In contrast, for branched OEIs BPEI(8) and BPEI(10) surface multilayer formation occurs over a wide range of OEI and SDS concentrations at pH 3 and 7, and at pH 10, the adsorption is mainly in the form of a monolayer. The results provide important insight into how the OEI architecture and pH can be used to control and manipulate the nature of the OEI/surfactant adsorption.